Chromatin plasticity in response to DNA damage: the shape of things to come - Adam, Salomé (DNA Repair (Amst), 2015)
DNA damage poses a major threat to cell function and viability by compromising both genome and epigenome integrity. The DNA damage response indeed operates in the context of chromatin and relies on dynamic changes in chromatin organization. Here, we review the molecular bases of chromatin alterations in response to DNA damage, focusing on core histone mobilization in mammalian cells. Building on our current view of nucleosome dynamics in response to DNA damage, we highlight open challenges and avenues for future development. In particular, we discuss the different levels of regulation of chromatin plasticity during the DNA damage response and their potential impact on cell function and epigenome maintenance.